MODEL NARASI DALAM NOVEL THE SATANIC VERSES KARYA SALMAN RUSDHIE - Puryanti, Lina (Balai Bahasa Jawa Timur, 2008)
This paper aims to analyze the narrative model used in The Satanic Verses novel by Salman Rusdhie as a writing strategy. The analysis shows that, in telling his narration, Rusdhie uses a hidden narrator as an actor who significantly controls the story and, in this way, magical realism is purposely employed to convey his messages. This narrative model produces a reading that the novel is offering a discourse of 'doubt' as an alternative over the text's single interpretation